Alumina and preparation method thereof, lithium battery separator and lithium battery

A simplified production process for aluminum oxide with low BET and narrow particle size distribution addresses the complexity and cost issues of traditional methods, enabling safer and more efficient lithium batteries by blocking current conduction holes during high current conditions.

CN115710005BActive Publication Date: 2024-12-13HUZHOU NANMU-NANO SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211461237.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2024-12-13
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

Traditional methods for producing high-purity alumina are complex and costly, limiting its widespread application in lithium batteries, and existing lithium battery separators face issues with perforation due to high current, leading to safety risks such as burning or explosion.

Method used

A simplified process for producing aluminum oxide involves mixing aluminum hydroxide with a mineralizer, heat treatment, grinding, pH adjustment, and spray drying to achieve alumina with low BET, high purity, and narrow particle size distribution, which is then used as a coating on lithium battery separators to block current conduction holes during high current conditions.

Benefits of technology

The resulting aluminum oxide coating enhances the safety and performance of lithium batteries by blocking current conduction holes during high current, allowing for high-power batteries with high energy density and reliable charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115710005B_ABST
    Figure CN115710005B_ABST
Patent Text Reader

Abstract

The present invention relates to an aluminum oxide and a preparation method thereof, a lithium battery separator and a lithium battery. The preparation method of aluminum oxide comprises: mixing aluminum hydroxide and a mineralizer uniformly and then performing heat treatment, obtaining an aluminum oxide precursor after sufficient reaction; grinding the aluminum oxide precursor until D50 is 1 μm to 3 μm to obtain a ground aluminum oxide precursor; mixing the ground aluminum oxide precursor with water to obtain a slurry, and then adjusting the pH value of the slurry to 6 to 8 to obtain a neutral slurry; mixing the neutral slurry and a dispersant uniformly and then grinding until the D50 of the aluminum oxide precursor in the neutral slurry is 0.3 μm to 1.0 μm, and D100 is less than 5 μm, to obtain a ground neutral slurry; and spray drying the ground neutral slurry, and then breaking up the agglomerated large particles after spray drying to obtain aluminum oxide. The above-mentioned aluminum oxide preparation method has a simple production process, can be mass-produced, has a cost advantage, and can prepare α-alumina with low BET, high purity and narrow particle size distribution by the above-mentioned preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to aluminum oxide and a preparation method thereof, a lithium battery separator and a lithium battery. Background Art

[0002] Lithium battery separator is a thin film with microporous structure (such as PE, PP, PE-PP composite film, etc.). For PP, PE or PP-PE composite lithium battery separator, when the current is too large, it is easy to cause perforation, which in turn causes the lithium battery to burn or explode. Fine alumina can be used as a coating material together with an adhesive and applied on the surface of PP or PE material to adjust the pores. This is because high-purity alumina has a crystal structure. When the current is too large, the material heats up, and the high-purity alumina coating material with a plate-like crystal structure will expand in volume, which will close the current conduction holes on the lithium battery separator, thereby blocking the current. When the temperature drops, the material volume will shrink, and the current conduction holes on the lithium battery separator will reopen. By utilizing the special physical and chemical properties of this material, the safety performance of lithium batteries can be greatly improved, thereby providing the possibility for high-power lithium batteries to have high energy density and safe and reliable charging and discharging.

[0003] Traditional high-purity fine alumina is obtained from organic aluminum salts by thermal decomposition, and the purity of the alumina produced by this method can reach 99.99%. However, the traditional preparation method has harsh and complex process conditions and high production costs, which is not conducive to widespread application. Summary of the invention

[0004] Based on this, it is necessary to provide an aluminum oxide with a simple production process and a preparation method thereof, a lithium battery separator and a lithium battery.

[0005] A method for preparing aluminum oxide comprises the following steps:

[0006] The aluminum hydroxide and the mineralizer are uniformly mixed and then heat treated to obtain an aluminum oxide precursor after sufficient reaction;

[0007] Grinding the aluminum oxide precursor until D50 is 1 μm to 3 μm to obtain a ground aluminum oxide precursor;

[0008] The ground alumina precursor is mixed with water to obtain a slurry, and then the pH value of the slurry is adjusted to 6 to 8 to obtain a neutral slurry;

[0009] The neutral slurry and the dispersant are mixed uniformly and then ground until the D50 of the aluminum oxide precursor in the neutral slurry is 0.3 μm to 1.0 μm and the D100 is less than 5 μm, to obtain a ground neutral slurry; and

[0010] The ground neutral slurry is spray-dried, and then the agglomerated large particles after spray drying are broken up to obtain aluminum oxide.

[0011] The above-mentioned aluminum oxide preparation method has a simple production process, can be mass-produced, and has cost advantages. Experimental verification shows that the above-mentioned aluminum oxide preparation method can prepare α-alumina with low BET, high purity and narrow particle size distribution, which is conducive to wide application.

[0012] In a feasible implementation, the aluminum hydroxide and the mineralizer are uniformly mixed and then heat treated. After sufficient reaction, the aluminum oxide precursor is obtained by:

[0013] After aluminum hydroxide and the mineralizer are evenly mixed, they are put into a heat treatment device, and then the temperature is increased to 1100°C / min-1500°C / min at a heating rate of 1°C / min-20°C / min, and after keeping the temperature for 1h-24h, an alumina precursor with a particle size D50 of 1μm-10μm is obtained; wherein the heat treatment equipment is a box furnace, a tubular furnace, a roller kiln, a push plate kiln or a rotary kiln.

[0014] In a feasible implementation, the mineralizer is boric acid; and / or the mass ratio of the aluminum hydroxide to the mineralizer is 100:(0.1-5).

[0015] In a feasible implementation, an organic acid is used to adjust the pH value of the slurry, and the organic acid is selected from at least one of citric acid, oxalic acid, acetic acid, oxalic acid and formic acid.

[0016] In a feasible implementation, the mass ratio of the neutral slurry to the dispersant is 100:(0.1-5); and / or

[0017] The solid content of the neutral slurry is 10% to 50%; and / or

[0018] The dispersant is polyethylene glycol with a molecular weight of 400 to 4000.

[0019] In a feasible implementation, the operation of breaking up the large agglomerated particles after spray drying is: using a disc jet mill to break up the large agglomerated particles after spray drying.

[0020] Alumina is prepared by any of the above-mentioned methods for preparing alumina, wherein the particle size D50 of the alumina is 0.3 μm to 1.0 μm, the particle size D100 of the alumina is less than 5 μm, and the purity of the alumina is above 99%.

[0021] The alumina of the present invention has the advantages of low BET, high purity and narrow particle size distribution, and is conducive to wide application.

[0022] In a feasible implementation, the specific surface area of ​​the aluminum oxide is 3m 2 / g~8m 2 / g, the pH value of the pure aqueous solution of aluminum oxide with a solid content of 30% is 8-9.

[0023] A lithium battery separator comprises a base film, at least one surface of the base film is provided with a coating, and the coating comprises the above-mentioned aluminum oxide.

[0024] The lithium battery separator of the present invention includes the above-mentioned aluminum oxide. Since the aluminum oxide of the present invention has the advantages of low BET, high purity and narrow particle size distribution, the lithium battery separator using the above-mentioned aluminum oxide has good performance and is conducive to wide application.

[0025] A lithium battery comprises the lithium battery separator mentioned above.

[0026] The aluminum oxide of the present invention can be used as a coating material on the surface of the base film to adjust the pores. This is because the high-purity aluminum oxide has a crystal structure. When the current is too large, the base film material heats up, and then the high-purity aluminum oxide coating material with a plate-like crystal structure will expand in volume, closing the current conduction holes on the lithium battery diaphragm, thereby blocking the current; when the temperature drops, the base film material will shrink in volume, and the current conduction holes on the lithium battery diaphragm will reopen. The special physical and chemical properties of aluminum oxide can greatly improve the safety performance of lithium batteries, thereby providing the possibility of high-power lithium batteries with high energy density and safe and reliable charging and discharging. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A flow chart of a method for preparing aluminum oxide according to one embodiment of the present invention;

[0028] Figure 2 is a particle size diagram of α-alumina in Example 1 of the present invention;

[0029] Figure 3 The XRD diffraction pattern of α-alumina of Example 1 of the present invention and the standard PDF card #10-1073 of α-alumina are shown. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0032] See also Figure 1 A method for preparing aluminum oxide according to an embodiment of the present invention comprises the following steps:

[0033] S10, mixing aluminum hydroxide and a mineralizer uniformly and then heat treating them to obtain an aluminum oxide precursor after sufficient reaction.

[0034] In one embodiment, the aluminum hydroxide and the mineralizer are uniformly mixed and then heat treated to obtain an aluminum oxide precursor after sufficient reaction. The operation is:

[0035] After aluminum hydroxide and the mineralizer are evenly mixed, they are put into a heat treatment device, and then the temperature is increased to 1100°C / min-1500°C / min at a heating rate of 1°C / min-20°C / min, and after keeping the temperature for 1h-24h, an alumina precursor with a particle size D50 of 1μm-10μm is obtained; wherein the heat treatment equipment is a box furnace, a tubular furnace, a roller kiln, a push plate kiln or a rotary kiln.

[0036] In one embodiment, the mineralizer is boric acid. Boric acid as a mineralizer can reduce the temperature of heat treatment and inhibit grain adhesion, thereby avoiding affecting the performance of alumina.

[0037] In one embodiment, the mass ratio of aluminum hydroxide to mineralizer is 100:(0.1-5).

[0038] In step S10, aluminum hydroxide is heat treated to decompose into an aluminum oxide precursor with larger particles. It should be noted that aluminum oxide in the present invention is an abbreviation and refers to α-aluminum oxide.

[0039] S20, grinding the aluminum oxide precursor obtained in step S10 until D50 is 1 μm to 3 μm, to obtain a ground aluminum oxide precursor.

[0040] In step S20, the aluminum oxide precursor obtained in step S10 may be ground by a ball mill or a disc jet mill.

[0041] S30, mixing the ground alumina precursor obtained in step S20 with water to obtain a slurry, and then adjusting the pH value of the slurry to 6-8 to obtain a neutral slurry.

[0042] In one embodiment, the solid content of the neutral slurry is 10% to 50%.

[0043] In one embodiment, an organic acid is used to adjust the pH value of the slurry, and the organic acid is selected from at least one of citric acid, oxalic acid, acetic acid, oxalic acid and formic acid. These types of organic acids can neutralize the alkaline substances on the surface of the alumina precursor and remove the polar substances on the surface of the alumina precursor during the subsequent drying process.

[0044] S40, mixing the neutral slurry obtained in step S30 with a dispersant uniformly and grinding until the D50 of the aluminum oxide precursor in the neutral slurry is 0.3 μm to 1.0 μm and the D100 is less than 5 μm, thereby obtaining a ground neutral slurry.

[0045] In one of the embodiments, the mass ratio of the neutral slurry to the dispersant is 100:(0.1-5).

[0046] In one embodiment, the dispersant is polyethylene glycol with a molecular weight of 400 to 4000. Polyethylene glycol with a molecular weight of 400 to 4000 as a dispersant helps to make the particles of the aluminum oxide precursor more uniformly dispersed during the grinding process, and grinds the aluminum oxide precursor into a spherical morphology.

[0047] S50, spray-drying the ground neutral slurry obtained in step S40, and then breaking up the large agglomerated particles after spray drying to obtain aluminum oxide.

[0048] In step S50, the spray drying operation is: drying the ground neutral slurry obtained in step S40 by a spray dryer. After the spray drying process, spherical or other spherical-like, such as ring-shaped, aluminum oxide particles can be obtained.

[0049] In one embodiment, the operation of breaking up the agglomerated large particles after spray drying is: using a disc jet mill to break up the agglomerated large particles after spray drying, so as to obtain aluminum oxide particles with smaller particle size.

[0050] The above-mentioned aluminum oxide preparation method has a simple production process, can be mass-produced, and has cost advantages. Experimental verification shows that the above-mentioned aluminum oxide preparation method can prepare α-alumina with low BET, high purity and narrow particle size distribution, which is conducive to wide application.

[0051] Alumina according to one embodiment is prepared by any of the above-mentioned methods for preparing alumina, and has a particle size D50 of 0.3 μm to 1.0 μm, a particle size D100 of less than 5 μm, and a purity of 99% or more.

[0052] In one embodiment, the specific surface area of ​​aluminum oxide is 3 m 2 / g~8m 2 / g, the pH value of the pure aqueous solution of aluminum oxide with a solid content of 30% is 8 to 9. At this time, the pH is in the neutral value range, which is conducive to the dispersion of the slurry to be coated later.

[0053] The alumina of the present invention has the advantages of low BET, high purity and narrow particle size distribution, and is conducive to wide application.

[0054] A lithium battery separator according to one embodiment includes a base film, at least one surface of the base film is provided with a coating layer, and the coating layer includes the above-mentioned aluminum oxide.

[0055] In one embodiment, the base film is a polyethylene film, a polypropylene film, or a composite film of a polyethylene film and a polypropylene film. In this case, the aluminum oxide of the present invention is used as a coating material on the surface of PP or PE materials to adjust the pores. At the same time, these types of base films have good wettability and adhesion, and respectively show good stability, are easy to coat, and are not easy to fall off. The product is more stable, can ensure the quality of lithium-ion battery separators, and improve the comprehensive performance of lithium-ion batteries.

[0056] The lithium battery separator of the present invention includes the above-mentioned aluminum oxide. Since the aluminum oxide of the present invention has the advantages of low BET, high purity and narrow particle size distribution, the lithium battery separator using the above-mentioned aluminum oxide has good performance and is conducive to wide application.

[0057] A method for preparing a lithium battery separator according to one embodiment comprises the following steps:

[0058] The above-mentioned aluminum oxide and auxiliary agent are mixed evenly to obtain a coating slurry; then the coating slurry is coated on at least one side of the surface of the base film, and after drying, a lithium battery separator is obtained.

[0059] In one embodiment, the auxiliary agent includes deionized water, a thickener, a dispersant and a binder; the mass ratio of aluminum oxide, deionized water, a thickener, a dispersant and a binder is (10-50): (50-80): (0.1-1): (0.1-2): (1-10). The thickener, the dispersant and the binder can be selected from the thickener, the dispersant and the binder commonly used in the art.

[0060] In one embodiment, the preparation method of the lithium battery separator is as follows: adding a thickener to deionized water and dispersing it for 0.5h to 1h, then adding alumina to the solution and dispersing it for 0.5h to 1h, then adding a dispersant and dispersing it for 0.5h to 1h, and then adding a binder and dispersing it for 0.5h to 1h to obtain a coating slurry; then applying the coating slurry to at least one side of the base film, and obtaining a lithium battery separator after drying.

[0061] In one embodiment, the thickener is CMC (sodium carboxymethyl cellulose).

[0062] The preparation method of the lithium battery separator of the present invention has simple process, and the prepared lithium battery separator has good performance, which is conducive to wide application.

[0063] A lithium battery according to one embodiment is characterized by comprising the above-mentioned lithium battery separator.

[0064] The aluminum oxide of the present invention can be used as a coating material on the surface of the base film to adjust the pores. This is because the high-purity aluminum oxide has a crystal structure. When the current is too large, the base film material heats up, and then the high-purity aluminum oxide coating material with a plate-like crystal structure will expand in volume, closing the current conduction holes on the lithium battery diaphragm, thereby blocking the current; when the temperature drops, the base film material will shrink in volume, and the current conduction holes on the lithium battery diaphragm will reopen. The special physical and chemical properties of aluminum oxide can greatly improve the safety performance of lithium batteries, thereby providing the possibility of high-power lithium batteries with high energy density and safe and reliable charging and discharging.

[0065] With reference to the above implementation contents, in order to make the technical solution of the present application more specific, clear and easy to understand, the technical solution of the present application is now exemplified. However, it should be noted that the contents to be protected by the present application are not limited to the following Examples 1 to 6.

[0066] Example 1

[0067] 100 g of boric acid mineralizer was added to 10 kg of aluminum hydroxide (d50: 3.14 μm) and mixed evenly, and then placed in a box furnace and heated to 1200° C. at a heating rate of 3° C. / min and kept warm for 18 hours to obtain an aluminum oxide precursor;

[0068] The aluminum oxide precursor is ground by a disc jet mill to a particle size of 1.543 μm to obtain a ground aluminum oxide precursor;

[0069] 6 kg of the ground alumina precursor was prepared into a slurry with pure water as a solvent and a solid content of 30%, and citric acid was added to adjust the pH value of the slurry to 7.5 to obtain a neutral slurry;

[0070] 6 g of PEG2000 dispersant was added to the neutral slurry, the mixture was evenly mixed, and then sand-milled until the D50 of the aluminum oxide precursor in the neutral slurry was 0.532 μm and the D100 was 3.22 μm, thereby obtaining a ground neutral slurry;

[0071] The ground neutral slurry was dried by a spray dryer, and finally subjected to a disc jet mill to break up the agglomerated large particles, thereby obtaining the α-alumina of Example 1.

[0072] The α-alumina of Example 1 was tested for particle size, and the obtained Figure 2 .from Figure 2It can be seen that the particle size distribution of the α-alumina of Example 1 is narrow.

[0073] The α-alumina of Example 1 was subjected to X-ray diffraction to obtain Figure 3 .from Figure 3 It can be seen that the substance prepared in Example 1 has the same diffraction peak as that of α-alumina in the standard PDF card #10-1073, indicating that the synthesized substance is α-alumina.

[0074] Example 2

[0075] 150 g of boric acid mineralizer was added to 10 kg of aluminum hydroxide (d50: 3.14 μm) and mixed evenly, and then placed in a box furnace and heated to 1300° C. at a heating rate of 3° C. / min and kept warm for 14 hours to obtain an aluminum oxide precursor;

[0076] The aluminum oxide precursor is ground by a disc jet mill to a particle size of 1.322 μm to obtain a ground aluminum oxide precursor;

[0077] 6 kg of the ground alumina precursor was prepared into a slurry with pure water as a solvent and a solid content of 20%, and citric acid was added to adjust the pH value of the slurry to 7.5 to obtain a neutral slurry;

[0078] 6 g of PEG2000 dispersant was added to the neutral slurry, the mixture was evenly mixed, and then sand-milled until the D50 of the aluminum oxide precursor in the neutral slurry was 0.887 μm and the D100 was 3.841 μm, thereby obtaining a ground neutral slurry;

[0079] The ground neutral slurry was dried by a spray dryer, and finally the agglomerated large particles were broken up by a disc jet mill to obtain the α-alumina of Example 2.

[0080] Example 3

[0081] 150 g of boric acid mineralizer was added to 10 kg of aluminum hydroxide (d50: 3.14 μm) and mixed evenly, and then placed in a box furnace and heated to 1200° C. at a heating rate of 3° C. / min and kept warm for 24 hours to obtain an aluminum oxide precursor;

[0082] The aluminum oxide precursor is ground by a disc jet mill to a particle size of 1.651 μm to obtain a ground aluminum oxide precursor;

[0083] 6 kg of the ground alumina precursor was prepared into a slurry with pure water as a solvent and a solid content of 40%, and citric acid was added to adjust the pH value of the slurry to 6.8 to obtain a neutral slurry;

[0084] 8 g of PEG4000 dispersant was added to the neutral slurry, the mixture was evenly mixed, and then sand-milled until the D50 of the aluminum oxide precursor in the neutral slurry was 0.668 μm and the D100 was 3.749 μm, thereby obtaining a ground neutral slurry;

[0085] The ground neutral slurry was dried by a spray dryer, and finally subjected to a disc jet mill to break up the agglomerated large particles to obtain the α-alumina of Example 3.

[0086] Example 4

[0087] 100 g of boric acid mineralizer was added to 10 kg of aluminum hydroxide (d50: 3.14 μm) and mixed evenly, and then placed in a box furnace and heated to 1300° C. at a heating rate of 3° C. / min and kept warm for 24 hours to obtain an aluminum oxide precursor;

[0088] The aluminum oxide precursor is ground by a disc jet mill to a particle size of 2.532 μm to obtain a ground aluminum oxide precursor;

[0089] 6 kg of the ground alumina precursor was prepared into a slurry with pure water as a solvent and a solid content of 30%, and citric acid was added to adjust the pH value of the slurry to 7.8 to obtain a neutral slurry;

[0090] 10 g of PEG2000 dispersant was added to the neutral slurry, the mixture was evenly mixed, and then sand-milled until the D50 of the aluminum oxide precursor in the neutral slurry was 0.718 μm and the D100 was 4.112 μm, thereby obtaining a ground neutral slurry;

[0091] The ground neutral slurry was dried by a spray dryer, and finally the agglomerated large particles were broken up by a disc jet mill to obtain the α-alumina of Example 4.

[0092] Example 5

[0093] 80 g of boric acid mineralizer was added to 10 kg of aluminum hydroxide (d50: 3.14 μm) and mixed evenly, and then placed in a box furnace and heated to 1200° C. at a heating rate of 5° C. / min and kept warm for 20 hours to obtain an aluminum oxide precursor;

[0094] The aluminum oxide precursor is ground by a disc jet mill to a particle size of 1.563 μm to obtain a ground aluminum oxide precursor;

[0095] 6 kg of the ground alumina precursor was prepared into a slurry with pure water as a solvent and a solid content of 30%, and citric acid was added to adjust the pH value of the slurry to 7.2 to obtain a neutral slurry;

[0096] 12 g of PEG2000 dispersant was added to the neutral slurry, and the mixture was evenly mixed and then sand-milled until the D50 of the aluminum oxide precursor in the neutral slurry was 0.698 μm and the D100 was 3.544 μm, thereby obtaining a ground neutral slurry;

[0097] The ground neutral slurry was dried by a spray dryer, and finally the agglomerated large particles were broken up by a disc jet mill to obtain the α-alumina of Example 5.

[0098] Example 6

[0099] 2.5 g of CMC was added to 1.54 kg of deionized water and dispersed at 3000 rpm for half an hour to obtain a CMC solution; 875 g of the alumina obtained in Example 1 was added to the CMC solution and dispersed at 3000 rpm for 1 hour, 3.75 g of PEG2000 and 3.75 g of LOPON885 were added and dispersed at 3000 rpm for half an hour, and 87.5 g of PAA emulsion was added and dispersed at 3000 rpm for half an hour to obtain a coating slurry; the coating slurry was then applied to one side of a PE base film with a thickness of 9 μm, and the lithium battery separator of Example 6 was obtained after drying.

[0100] Performance Testing:

[0101] (1) The D50, D100, BET, pH value, moisture content and purity of alumina of α-alumina of Examples 1 to 5 were tested. The testing method is as follows. The test results are shown in Table 1.

[0102] Particle size determination: Mastersizer 2000 laser particle size analyzer was used for determination.

[0103] BET test method: The test is carried out according to the national standard GB / T19587-2004 "Determination of specific surface area of ​​solid materials by gas adsorption BET method".

[0104] pH value test method: prepare α-alumina powder to 30% solid content and use a pH meter to measure the pH value of the solution.

[0105] Moisture test method: Determined by Karl Fischer moisture meter.

[0106] Alumina content test method: Determined by ICP-MS mass spectrometer.

[0107] Table 1 Performance test results of α-alumina of Examples 1 to 5

[0108]

[0109] As can be seen from Table 1, the D50 of the α-alumina of Examples 1 to 5 is 0.3 μm to 1.0 μm, the D100 is less than 5 μm, the BET is low, the water content is low, and the purity is above 99%.

[0110] (2) The thickness, air permeability increase, peel strength and puncture strength of the lithium battery separator of Example 6 were tested. The test method is as follows. The test results are shown in Table 2.

[0111] Thickness test method: Stack eight layers of diaphragm and measure with a micrometer.

[0112] Test method for air permeability added value: measured using an air permeability tester.

[0113] Peel strength test method: measured using a universal tensile testing machine.

[0114] Puncture strength test method: Test in accordance with GB / T23318-2009 standard.

[0115] Table 2 Performance test results of lithium battery separator of Example 6

[0116] Example Coating thickness Membrane moisture Increased breathability Peel strength Puncture strength Example 6 3.1μm 589ppm 25.838s / 100ml 65n / mm 555.1gf

[0117] It can be seen from Table 2 that the lithium battery separator of Example 6 of the present invention has lower membrane moisture, better air permeability, and higher peel strength and puncture strength, indicating that the lithium battery separator of Example 6 of the present invention has better performance.

[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0119] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing aluminum oxide, characterized in that: The steps include: The aluminum hydroxide and the mineralizer are uniformly mixed and then heat treated to obtain an aluminum oxide precursor after sufficient reaction; Grinding the aluminum oxide precursor until D50 is 1 μm to 3 μm to obtain a ground aluminum oxide precursor; The ground alumina precursor is mixed with water to obtain a slurry, and then the pH value of the slurry is adjusted to 6 to 8 to obtain a neutral slurry; The neutral slurry and the dispersant are mixed uniformly and then ground until the D50 of the aluminum oxide precursor in the neutral slurry is 0.3 μm to 1.0 μm and the D100 is less than 5 μm, thereby obtaining a ground neutral slurry; as well as The ground neutral slurry is spray-dried, and then the agglomerated large particles after spray drying are broken up to obtain aluminum oxide; Wherein, the mass ratio of the neutral slurry to the dispersant is 100:(0.1-5), and the solid content of the neutral slurry is 10%-50%; The neutral slurry includes the ground alumina precursor and water; the specific surface area of ​​the prepared alumina is 3m 2 / g~8m 2 / g.

2. The method for preparing aluminum oxide according to claim 1, characterized in that: The aluminum hydroxide and the mineralizer are uniformly mixed and then heat treated. The operation of obtaining the aluminum oxide precursor after sufficient reaction is as follows: After aluminum hydroxide and the mineralizer are evenly mixed, they are put into a heat treatment device, and then the temperature is increased to 1100°C / min-1500°C / min at a heating rate of 1°C / min-20°C / min, and after keeping the temperature for 1h-24h, an alumina precursor with a particle size D50 of 1μm-10μm is obtained; wherein the heat treatment equipment is a box furnace, a tubular furnace, a roller kiln, a push plate kiln or a rotary kiln.

3. The method for preparing aluminum oxide according to claim 1 or 2, characterized in that: The mineralizer is boric acid; and / or the mass ratio of the aluminum hydroxide to the mineralizer is 100:(0.1-5).

4. The method for preparing aluminum oxide according to claim 1, characterized in that: The pH value of the slurry is adjusted by using an organic acid, wherein the organic acid is selected from at least one of citric acid, oxalic acid, acetic acid, oxalic acid and formic acid.

5. The method for preparing aluminum oxide according to claim 1, characterized in that: The dispersant is polyethylene glycol with a molecular weight of 400 to 4000.

6. The method for preparing aluminum oxide according to claim 1, characterized in that: The operation of breaking up the large agglomerated particles after spray drying is as follows: using a disc jet mill to break up the large agglomerated particles after spray drying.

7. Aluminum oxide, characterized in that: The aluminum oxide is prepared by the method for preparing aluminum oxide according to any one of claims 1 to 6, wherein the particle size D50 of the aluminum oxide is 0.3 μm to 1.0 μm, the particle size D100 of the aluminum oxide is less than 5 μm, and the purity of the aluminum oxide is above 99%.

8. The aluminum oxide according to claim 7, characterized in that The specific surface area of ​​the aluminum oxide is 3m 2 / g~8m 2 / g, the pH value of the pure aqueous solution of aluminum oxide with a solid content of 30% is 8-9.

9. A lithium battery separator, characterized in that: It comprises a base film, at least one surface of which is provided with a coating, and the coating comprises the aluminum oxide according to claim 7 or 8.

10. A lithium battery, characterized in that: Including the lithium battery separator as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of superfine low-sodium alpha-alumina powder with high activity

    CN104229844A

  • Preparation method for high-purity ultrafine alumina used for lithium battery ceramic diaphragm

    CN105347778A

  • Preparation method of low-sodium spherical nano alpha-alumina powder

    CN110526270A